Demographic Transition in Kerala Revisited - P. N. Mari Bhat and S. Irudaya Rajan (Economic and Political Weekly, Vol. 25, No. 35/36 (Sep. 1-8, 1990), 1990)
Many competing hypotheses about Kerala's demographic transition have flourished and remained untested for long. This article undertakes a thorough review of demographic trends in Kerala by a careful scrutiny of evidence presented by various data sources. By employing a quantitative approach and using data for districts in and around Kerala, the authors test some of the hypotheses put forward to explain the shift in levels of birth and death rates. The article also briefly discusses the implications of the current declines for the future of the Kerala economy and assesses the prospects for a similar change elsewhere in India